Opportunities and Obstacles to Marketing Through AI: Theoretical study - Zakia Omer (تنمیة الرافدین)
Integrating artificial intelligence (AI) into marketing practices has significantly transformed the industry landscape, offering substantial opportunities and notable challenges. Integrating artificial intelligence (AI) has profoundly transformed marketing, presenting significant opportunities and critical challenges. This study investigates balancing these opportunities and challenges to achieve optimal marketing performance while maintaining customer trust. By adopting a qualitative approach that combines a literature review, case study analysis, and expert interviews, the research explores AI's potential to enhance marketing operations. It addresses the obstacles associated with its adoption. This paper critically examines AI's opportunities, including its capacity to streamline operations, manage vast datasets, and deliver tailored marketing strategies. Simultaneously, it addresses the obstacles associated with AI implementation, such as the complexity of integrating AI systems, data privacy concerns, and the challenges of adapting to rapid technological changes. By analysing these dimensions, the paper aims to comprehensively understand how AI can be harnessed effectively in marketing while navigating the inherent difficulties. The findings highlight that AI facilitates task automation, delivers precise analytics, and enables personalised marketing strategies. However, its implementation is hindered by privacy concerns, technical complexities, and ethical considerations. The study underscores the importance of strategic planning, fostering an organizational culture of innovation, and addressing ethical and technical challenges. It recommends the development of flexible governance frameworks and collaborative approaches between humans and AI to achieve excellence in marketing.